Improving students' literacy and numeracy skills at Sekolah Dasar Negeri 1 Liabuku, Baubau City - Rimayasi Rimayasi; Eka Rosmita Sari; Nurmawati Nurmawati (Universitas Muhammadiyah Magelang, 2024)
This community service activity is based on the low numeracy and literacy skills of students at SD Negeri 1 Liabuku, Baubau City. The aim of this service is to explore and enhance students' literacy and numeracy skills. The participants in this PKM activity were students from SD Negeri 1 Liabuku, Baubau City. This service activity takes the form of tutoring, which aims to improve and familiarize children with literacy and numeracy. The activity is implemented in three stages: the planning stage, implementation stage, and evaluation stage. The result of this service is a comprehensive and structured numeracy and literacy program at SD Negeri 1 Liabuku, Baubau City. The implementation of the program is aligned with three stages: habituation, development, and learning. Using a learning-through-play model and learning media, students' numeracy and literacy skills both inside and outside the classroom can significantly influence the development of their respective talents and skills.